Evaluation of Anti-Denaturation Property and Anti-Oxidant Activity of Traditionally used Medicinal Plants - N.DUGANATH; S.RUBESH KUMAR; R.KUMANAN; K.N.JAYAVEERA (International Journal of Pharma and Bio Sciences, 2010)
The antigenic property of the denatured proteins leads to some of the diseases like serum sickness, glomerulonephritis, rheumatoid arthritis and systemic lupus erythematosus. Metabolism of xenobiotics leads to the production of reactive oxygen species (ROS), which leads to oxidative stress. Many literatures stated that, chronic oxidative stress is one of the important causes for the production of auto antibodies which leads to autoimmune diseases. Different parts of Ventilago maderaspatana Geartn, Acacia nilotica linn, and Polyalthia longifolia were powdered and extracted by cold percolation using ethanol. The extracts were subjected for invitro protein anti-denaturation using Bovine serum albumin and reducing antioxidant activity. All the extracts have shown mild to moderate anti-denaturation and antioxidant activity. Among them Acacia nilotica showed anti-denaturation percentage inhibition of 97% at 1µg/ml. 1whereas the standard drug (Diclofenac sodium) showed a percentage inhibition of 66% at The result also shows that Acacia nilotica Linn has good reducing property than other plant extracts.